Pengembangan Modul Reaksi Reduksi Oksidasi Berbasis Inkuiri Terbimbing Terintegrasi Al Quran untuk Kelas X Madrasah Aliyah (MA) - Maury Tania; Iryani Iryani (Universitas Negeri Padang, 2022)
Chemistry learning in the 2013 Curriculum using guided inquiry which applied scientific approach can be presented in a module. The module was integrated with the Quran to fulfil Local Government Regulation No. 2 the Year 2019 and following core competence 1 in the 2013 Curriculum. The goal of the research was to produce and test the validity of the Quran integrated guided inquiry module on redox reaction topic for 10th Grade of Madrasah Aliyah (MA). The research used the Plomp model which has stages: preliminary research, prototyping stage, and assessment. The instrument is a validity questionnaire for teachers and lecturers. The V Aiken formula is used to calculate the validity value. The validation test revealed that Aikens V had an average value of 0.83. This indicates that the module is categorized as valid based on Aikens V category.